2010
DOI: 10.1111/j.1365-2133.2010.09828.x
|View full text |Cite
|
Sign up to set email alerts
|

Vitiligo linked to stigmatization in British South Asian women: a qualitative study of the experiences of living with vitiligo

Abstract: Bradford Scholars -how to deposit your paper Overview Copyright check• Check if your publisher allows submission to a repository.• Use the Sherpa RoMEO database if you are not sure about your publisher's position or email openaccess@bradford.ac.uk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 12 publications
3
74
0
3
Order By: Relevance
“…psoriasis) (31,32). The disfigurement, which is caused by skin diseases like vitiligo and psoriasis lead to high levels of experienced stigmatisation and shame (32,33). The feeling of being stigmatised again potentially causes high levels of psycho-social stress and has considerable impact on the patients' QoL especially on an emotional level (16,34), a state which again can be associated with a higher vegetative arousal.…”
Section: Discussionmentioning
confidence: 98%
“…psoriasis) (31,32). The disfigurement, which is caused by skin diseases like vitiligo and psoriasis lead to high levels of experienced stigmatisation and shame (32,33). The feeling of being stigmatised again potentially causes high levels of psycho-social stress and has considerable impact on the patients' QoL especially on an emotional level (16,34), a state which again can be associated with a higher vegetative arousal.…”
Section: Discussionmentioning
confidence: 98%
“…Some of the from schools due to frequent tor visits and the taunting they experienced at school (10). Vitiligo was also noted to be a barrier to marriage (11). For ) were not allowed to get jobs and were kept away from getting married and were uninvited to marriages because their old ancient and religious beliefs.Vitiligo was referred to as 'Kilas' in rigvedas, which Vitiligo is an acquired tion disorder of great concern affecting 1-4% of , Saudi Arabia, between January and August 2010.It was reported that more than half of the participants (58.2%, 523 of 899) would sympathize with vitiligo patients.…”
mentioning
confidence: 99%
“…Thompson et al 46 see a need in the UK for remedying, especially in Asian women, spoiled identity and being shame-prone with more attention to cultural sensitivity and intergenerational beliefs.…”
Section: Treatmentmentioning
confidence: 99%
“…Taking into account the potential dangers of using skin-lightening agents, it is important to educate people on the adverse effects of these treatments and help them realize that 'black really is beautiful'. Headings discussed by Thompson et al 46 include 'spoiled identity', being 'hidden away', loss of ethnic identity, appearance shame and disgust, 'intimacy impossible', avoidance and concealment, confronting and explaining, over compensation, denial, wishful thinking and minimizing.…”
Section: Black Is Beautiful: Is Skin Colour Of Public Health Significmentioning
confidence: 99%